2019
DOI: 10.1016/j.amepre.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette Use Among Young Adults in the U.S.

Abstract: Introduction: Use of e-cigarettes is increasing among young adults in the U.S. Whether ecigarette use serves as an aid to smoking reduction or cessation among young adults remains a matter of contention. This analysis examines patterns of e-cigarette use in relation to cigarette smoking in a nationally representative sample of U.S. young adults. Methods: Data were analyzed from nationally representative U.S. adults, aged 18 to 35 years (n=12,415), in the 2012-2013 National Epidemiologic Survey on Alcohol and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 43 publications
2
24
2
Order By: Relevance
“…Extant evidence on the efficacy of e-cigarettes is equivocal [4,13,14,24,55]. A US report using nationally representative data found that only 13% of young adult lifetime e-cigarette users reported using e-cigarettes as a cessation aid and these individuals were less likely to report cessation in the pastyear [56]. It is possible that, because of nicotine in ecigarettes (even in e-cigarettes labelled nicotine-free [53]), young adults who try to quit using nicotinecontaining e-cigarettes in fact contribute to or increase their ND level [25] leaving them craving nicotine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extant evidence on the efficacy of e-cigarettes is equivocal [4,13,14,24,55]. A US report using nationally representative data found that only 13% of young adult lifetime e-cigarette users reported using e-cigarettes as a cessation aid and these individuals were less likely to report cessation in the pastyear [56]. It is possible that, because of nicotine in ecigarettes (even in e-cigarettes labelled nicotine-free [53]), young adults who try to quit using nicotinecontaining e-cigarettes in fact contribute to or increase their ND level [25] leaving them craving nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis posits that e-cigarette users could decrease the number of cigarettes smoked because e-cigarettes deliver nicotine at similar rates, making them as or more satisfying than traditional nicotine replacement therapies, but contributing more to ND and sustained smoking [25]. Olfson et al (2019) [56] reported that e-cigarette users were 2.3 times more likely to be daily cigarette smokers than non-e-cigarette users, and 3.6 times more likely to report a tobacco use disorder. Recent longitudinal findings concur that dual use (cigarettes and e-cigarettes) was associated with an increase in e-cigarette frequency, nicotine exposure and ND in adolescent e-cigarette users with minimal cessation benefits [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The labelled nicotine ‘strength’ is available in a wide range, most commonly 0–24 mg/ml . Popularity of EC has increased dramatically in recent years, especially among adolescents . For new EC users who smoke tobacco, recent US evidence suggests that their use could pose a higher risk for the development of tobacco use disorder than daily cigarette smoking alone .…”
Section: Introductionmentioning
confidence: 99%
“…Popularity of EC has increased dramatically in recent years, especially among adolescents . For new EC users who smoke tobacco, recent US evidence suggests that their use could pose a higher risk for the development of tobacco use disorder than daily cigarette smoking alone . There has also been an increased interest globally in the safety of EC versus traditional cigarettes, and many agree that ECs can provide a harm reduction strategy versus actual tobacco exposure .…”
Section: Introductionmentioning
confidence: 99%